The Role of Learning Media in Enhancing Students’ Learning Interest in Islamic Education Subjects - Zhafirah Mazaya Hidayat; Cut Aisyah Salsabilla; Vika Aini (Yayasan Rahmat Islamiyah, 2026)
This study aims to analyze the role of learning media in enhancing students’ learning interest in Islamic Education subjects. This research employed a qualitative approach using a descriptive study method. Data collection techniques included observation, interviews, and documentation. The research subjects consisted of Islamic Education teachers and students involved in the learning process. The findings revealed that the use of learning media had a positive impact on students’ learning interest. Learning media created a more engaging, interactive, and enjoyable learning atmosphere, encouraging students to participate actively in classroom activities. Furthermore, the use of media such as images, videos, digital presentations, and audio-visual materials helped students understand Islamic Education materials more easily and effectively. Teachers also became more creative in delivering instructional content. Therefore, learning media play an important role in enhancing students’ learning interest in Islamic Education subjects.